Microplastics Effects on Reproduction and Body Length of the Soil-Dwelling Nematode Caenorhabditis elegans - Schöpfer, Lion; Menzel, Ralph; Schnepf, Uwe; Ruess, Liliane; Marhan, Sven; Brümmer, Franz; Pagel, Holger; Kandeler, Ellen (Frontiers in Environmental Science, 2020)
Microplastics (MP) are pervasive in the environment. There is ample evidence of negative MP effects on biota in aquatic ecosystems, though little is known about MP effects in terrestrial ecosystems. Given numerous entry routes of MP into soils, soil organisms are likely to be exposed to MP. We compared potential toxicological effects of MP from (i) low-density polyethylene (LDPE) (mean diameter ± standard deviation: 57 ± 40 μm) and (ii) a blend of biodegradable polymers polylactide (PLA) and poly(butylene adipate-co-terephthalate) (PBAT) (40 ± 31 μm) on the reproduction and body length of the soil-dwelling bacterivorous nematode Caenorhabditis elegans. Feed suspensions without (control) or with MP (treatments) at concentrations of 1, 10, and 100 mg MP L–1 were prepared and nematodes were exposed to those suspensions on agar plates until completion of their reproductive phase (∼6 days). Using Nile red-stained PLA/PBAT MP particles and fluorescence microscopy, we demonstrated the ingestion of MP by C. elegans into pharynges and intestines. Under MP exposure, nematodes had fewer offspring (up to 22.9%) compared to nematodes in the control group. This decline was independent on the plastic type. We detected a tendency toward greater decreases in offspring at higher concentrations. Despite hints of negative effects on nematode body length under MP exposure, we could not derive a consistent pattern. We conclude that in MP-contaminated soils, the reproduction of nematodes, central actors in the soil food web, can be affected, with potentially negative implications for key soil functions, e.g., the regulation of soil biogeochemical cycles.